The Implementation of Immunization Cold Chain Management in Surabaya City - Alfilia Lusita; Fariani Syahrul; Ponconugroho Ponconugroho (Jurnal Berkala Epidemiologi, 2021)
Background: Immunization success rates can be determined by several factors. The factors that can cause occurrences of immunization preventable disease (PD3I) cases include the quality of the cold chain and invalid doses of immunization medicines. Purpose: The aim of this research was to analyze the implementation of cold chain management in the city of Surabaya. Methods: This research was conducted as a descriptive study with a cross-sectional research design. The population consisted of all primary health care centers in the city of Surabaya, and the data used were secondary data, guided by interviews with informants. Results: The majority of cold chain management personnel were found to have a medical education background of 98.42%, and primary health care workers have received cold chain-related training (100%). All primary health care equipment has a 100% cold chain. The completeness of cold chain reporting was 93.51%, and the accuracy of the cold chain reporting was 71.52%. Regarding the quality of the equipment, some vaccine refrigerators were found 12% of vaccine refrigerators were found not to be in optimal condition, and 14% of temperature monitoring devices was not activated. Conclusion: The implementation of cold chain management in public health center and the availability of equipment in the Surabaya City are going well, although there are still some problems such as undisciplined reporting and inadequate quality of tools for cold chain implementation as well as the discovery of vaccine refrigerators easily leaks, and their temperature can rise easily.